RecO-mediated DNA homology search and annealing is facilitated by SsbA - Manfredi, Candela; Suzuki, Yuki; Yadav, Tribhuwan; Takeyasu, Kunio; Alonso, Juan C (Nucleic acids research, 2010)
Bacillus subtilis RecO plays a central role in recombinational repair and genetic recombination by (i) stimulating RecA filamentation onto SsbA-coated single-stranded (ss) DNA, (ii) modulating the extent of RecA-mediated DNA strand exchange and (iii) promoting annealing of complementary DNA strands. Here, we report that RecO-mediated strand annealing is facilitated by cognate SsbA, but not by a heterologous one. Analysis of non-productive intermediates reveals that RecO interacts with SsbA-coated ssDNA, resulting in transient ternary complexes. The self-interaction of ternary complexes via RecO led to the formation of large nucleoprotein complexes. In the presence of homology, SsbA, at the nucleoprotein, removes DNA secondary structures, inhibits spontaneous strand annealing and facilitates RecO loading onto SsbA-ssDNA complex. RecO relieves SsbA inhibition of strand annealing and facilitates transient and random interactions between homologous naked ssDNA molecules. Finally, both proteins lose affinity for duplex DNA. Our results provide a mechanistic framework for rationalizing protein release and dsDNA zippering as coordinated events that are crucial for RecA-independent plasmid transformation.